2017
DOI: 10.1016/j.conbuildmat.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between acoustic emission distribution and stress variation through the depth of RC beam cross sections

Abstract: Highlights The acoustic emission distribution through the depth of RC beam sections is studied. AE parameters can characterise behaviours of RC beams in the depth direction. AE event intensity shows a higher correlation than energy-based parameters in the study. The correlation between AE and stress responses was demonstrated to be very strong. A new option for estimating stress levels in engineering and science is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…The authors think this may result from the low AE activity in this stage, especially considering the fact that AEs are by‐products of great stresses and the magnitude of the load applied on the specimen at that time was still very small (less than 17.523 kN on Beam 12‐5). In addition, similar conclusion was drawn in previous work . In summary, the correlation between the distributions of the shear stresses and AEs is not clear when the beam is in the elastic stage.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The authors think this may result from the low AE activity in this stage, especially considering the fact that AEs are by‐products of great stresses and the magnitude of the load applied on the specimen at that time was still very small (less than 17.523 kN on Beam 12‐5). In addition, similar conclusion was drawn in previous work . In summary, the correlation between the distributions of the shear stresses and AEs is not clear when the beam is in the elastic stage.…”
Section: Resultssupporting
confidence: 87%
“…According to the findings obtained in this study and previous work, it was found the correlations observed in specimens failed in the flexural mode or the shear mode shared common features and also demonstrated significant distinctions. Two shared features are briefed as follows.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations